Necrotizing Fasciitis Caused by Photobacterium damselae: The First Case in Portugal - Guimaraes, Diogo (2021)
Necrotizing fasciitis is a severe soft tissue infection with a high mortality rate and therefore requires emergent surgical treatment. Several microorganisms can cause this infection, Photobacterium damselae being one of them, with only eight cases previously published in the literature. We report the first ever case of necrotizing fasciitis, caused by this microorganism, in Portugal. In this case report the patient survived after several debridement procedures and reconstruction of the upper limb with acellular dermal matrix and skin graft. A brief review of the Photobacterium damselae soft tissue infection reports as well as the clinical presentation, diagnosis, pathophysiology and treatment of necrotizing fasciitis can also be found in this paper.